HUBUNGAN KONSUMSI SUSU DENGAN TINGGI BADAN DAN PRESTASI BELAJAR PADA SISWA/I DI SEKOLAH DASAR MUHAMMADIYAH 02 KAMPUNG DADAP MEDAN - Fahrun Nisa; Zulhaida Lubis; Albiner Siagian (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2017)
School-aged children are vulnerable to health and nutrition probelms. Various nutritional problems are common in school age. This is due to a lack of nutritional intake required by children. Milk is one of the food which known to contain high protein and calcium nutrients which are needed by school-aged children. The purpose of this study was to determine the relationship between milk consumption with body-height and student achievement in Muhammadiyah Elementary School 02 Kampung Dadap Medan. This is an observational research with cross-sectional design. The sample in this research is all of the students in Muhammadiyah Primary School 02 Kampung Dadap Medan started from class II to V which amounted to 88 students. The data of student’s milk consumption were collected by interview using 24 hour food recall form and food frequency done by the researcher. Body-height was measured by microtoise. The data of learning achievement were taken from student report result of the first semester of year 2016/2017. The result of the research shows that the height of the students of Muhammadiyah 02 primary school in Kampung Dadap Medan is still in the category below normal (44,3%). Most of the student there are having a good school achievement (67%). There is a significant relationship between protein and calcium adequacy of milk consumption with student height with p value = 0,0001. Meanwhile, there are no significant relationship between protein and calcium adequacy of milk consumption with learning achievement withp value = 0,193 and p = 0,239. Suggestions for the school to help increase the student’s milk consumption because it is beneficial for growth and development. In addition, students are advised to consume milk 2 glasses per day to meet the daily intake of a more optimal nutrition.   Keywords: Milk consumption, body height, learning achievement, student of elementary school